The effect of concrete fatigue on the cyclic behaviour of composite dowels - derivation of a design approach based on experimental findings. (15th February 2022) - Christou, Georgios; Schmidt, Christopher; Hegger, Josef; Classen, Martin
Abstract: Composite dowels as shear connectors between the two partners steel and concrete are gaining attention in both building and bridge structures as a substitute for conventional shear connectors. Advantages such as their high load-bearing capacity and stiffness and their robustness in case of cyclic loading distinguish them from other shear connectors. However, the existing regulations for the fatigue design of composite dowels are very conservative since the experimental data and theoretical background on which the regulations are based are still not sufficient. Therefore, the advantageous cyclic load-bearing behaviour of composite dowels cannot yet be effectively considered in design. Within the scope of this article, the load-bearing behaviour of composite dowels under cyclic loading is analysed in detail based on recent experimental investigations. An existing approach to determine the characteristic dowel curve of clothoid-shaped composite dowels is refined and a new model is proposed allowing to determine the lifespan of composite dowels under cyclic loads. This model is capable of predicting the service life of composite dowels considering geometrical and load-dependent parameters.